Reformulasi Pendekatan Wisata Halal: Perspektif Maqāṣid Syarī‘ah dalam Masyarakat Plural - Arinaldi Nugraha (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
The development of halal tourism in Indonesia continues to accelerate along with increasing awareness of halal lifestyles and support from government policies. However, its implementation in plural areas such as Bali, Lake Toba, and Labuan Bajo often causes social resistance due to symbolic and non-contextual approaches. This study aims to evaluate the tension between welfare and potential marginalization in the implementation of halal tourism, using the perspective of maqāṣid shari'ah as the main analytical framework. The method used is a literature study with a qualitative descriptive approach, through a review of scientific literature, policy documents, and public opinion from online media. The research findings show that halal tourism in homogeneous areas such as Lombok has succeeded in presenting welfare through a participatory approach that strengthens the values ​​of ḥifẓ al-dīn and ḥifẓ al-māl. Conversely, in plural areas, policies that do not involve local communities actually risk disrupting ḥifẓ al-nafs and ḥifẓ al-‘irḍ. The conclusion of this study emphasizes the importance of an ethical-participatory approach in developing halal tourism in order to comply with the principle of maqāṣidik justice. Therefore, the use of the term “Muslim-friendly tourism” and cross-community involvement are recommended in order to create social harmony and economic sustainability in plural societies.